Conservation Agriculture Long-Term Trial at Msekera Research Station, Zambia - International Maize and Wheat Improvement Center; Zambian Agriculture Research Institute (International Food Policy Research Institute, 2020)
The present data is from a long-term trial set at Msekera Research Station in Zambia to monitor and evaluate the long-term effects of conservation agriculture practices on soil quality, soil water dynamics, weeds, pests/diseases, and crop yield. This trial was conducted from 2012 to 2020. The ten treatments including control were: T1: Control plot 1 (CPM1): traditional farmers practice mouldboard plough on the flat, maize as a sole crop, no residue retention, stubble incorporated into the row for the following season. T2: Control plot 2 (CPM2); ridge and furrow system dug by hand, maize as a sole crop, no residue retention, stubble incorporated into the row for the following season T3: Basins (BAM), residue retention on the surface, maize as a sole crop T4: Dibble stick (DISM), residue retention on the surface, maize as a sole crop T5: Direct seeder (DSM), residue retention on the surface, maize as a sole crop T6: Direct seeding maize/cowpea intercropping (DS-M/C), 90cm rows, residue retention on the surface T7: Direct seeding cowpea (Cowpea-maize rotation) (DS-MC), residue retention on the surface T8:Direct seeding maize (Maize-cowpea rotation) (DS-CM), residue retention on the surface T9:Direct seeding soya (Soybean-maize rotation) (DS-MS), residue retention on the surface T10: Direct seeding maize (Maize-soybean rotation) (DS-SM), residue retention on the surface